Meta-analysis of 327 cases of exertional rhabdomyolysis - Vasques, Marco Agassiz Almeida; Gomes, Leani Falcão (Revista de Medicina e Saúde de Brasília, 2019)
Exertional rhabdomyolysis (ER) is a potentially serious condition that usually requires hospitalization and intravenous hydration to prevent complications such as acute renal failure. The literature on this subject is predominantly of case reports. This paper compiles data of 327 cases of ER published over the ten-year period (2008-2017). There was a predominance of young men with reports of exercises that included long duration, high load or high number of repetitions, above the physical abilities of the individuals. The classic triad of myalgia, dark urine and muscle weakness was reported only in 17% of the patients. Symptom onset occurred on average 2 days after exercise (ranging from 0 to 14 days). Mean serum creatine kinase levels of 71,277 U/L were reported at admission and mean peak levels of 85,778 U/L reported around the third day after muscle damage (up to 1,454,952 U/L). The most frequently involved muscles were in the lower extremities (41%), but ER was reported in almost all body regions. Acute renal failure was reported in 7% of cases. Knowledge of the main aspects of the pathophysiology of this disease is important for the design of preventive measures, especially among professionals and people involved in physical activity.